If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying z + 4(2 + 3) = 15 Combine like terms: 2 + 3 = 5 z + 4(5) = 15 Multiply 4 * 5 z + 20 = 15 Reorder the terms: 20 + z = 15 Solving 20 + z = 15 Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '-20' to each side of the equation. 20 + -20 + z = 15 + -20 Combine like terms: 20 + -20 = 0 0 + z = 15 + -20 z = 15 + -20 Combine like terms: 15 + -20 = -5 z = -5 Simplifying z = -5
| 73-17+46= | | W/7-12=-1 | | -3x-24=x+8 | | x+.06x=106 | | (X-1)(x-2)+4=(x-1)+3 | | W/7-=-1 | | 2x^3-3x^2-x=0 | | 2x-37=x-5 | | 3(6-2x)+1=2(1x+2)-5x | | 0=4t+72 | | 1+-8z=-15 | | -y+6=11 | | 12x+5x=13x | | 2x-(x-5)=7-6(x-2) | | 48-6x=4x | | 5x+6y=6y+5x | | (9/10)*(4/5) | | -5x=4y+8 | | n+6=-16 | | 6s+s-4s-3s+4s=16 | | X^2+y^2+3x-2y=0 | | 5=3-(4-2) | | -4j-3j-j+j=20 | | 23=w+6 | | 1-2tan^2x=-tan^2x | | 0.25(y-4)+.03y=0.18y-0.05(40) | | j+j-j=11 | | -16t^2+84t+112=0 | | 6.3/0.9-(-4.1)x(-0.4) | | 8y-2(5+2y)=7y-16 | | 2 = 12(9x+8) | | -3(3x-3)-9=-2(7x+3)-3 |